A facile construction of quaternized polymer brush-grafted graphene modified polysulfone based composite anion exchange membranes with enhanced performance. Issue 56 (25th May 2016) - Hu, Bo; Liu, Lingdi; Zhao, Yanxu; Lü, Changli
Abstract : Novel quaternized polymer brush-functionalized graphenes (QPbGs) were synthesized and a series of composite anion exchange membranes for alkaline fuel cells were fabricated by incorporating different amounts of QPbGs into quaternized polysulfone. Abstract : In order to prepare a new type of graphene modified composite anion exchange membranes (AEMs) with good dispersity, high conductivity and low permeability, quaternized polymer brush-functionalized graphenes (QPbGs) were successfully synthesized from graphene oxide (GO) by a hydrothermal process and "grafting from" method based on a reversible addition fragmentation chain transfer polymerization. By incorporating different amounts of QPbGs into a quaternized polysulfone (QPSU) matrix, the obtained composite membranes with dispersed QPbGs showed good thermal stability, oxide stability and mechanical properties. As shown in transmission electron microscope images, the concentration of ionic clusters with uniform distribution of membranes increased when the content of QPbGs was below 1 wt%, illustrating that the quaternary ammonium groups in polymer brushes may provide more ionic pathways. The bicarbonate conductivity of composite membranes increased with increasing content of QPbGs and showed the highest conductivity of 0.056 S cm −1 at 80 °C. The other properties including ion exchange capacity, water uptake, swelling ratios, methanol permeability and alkaline resistance of membranes were all improved with increasing amount of QPbGs fillers. Our study showed that AEMs with enhanced performance can be achieved by incorporating an appropriate content of QPbGs into the QPSU matrix.